Метод расчета переходных режимов гребных электроэнергетических установок электроходов - Яровенко, В.А.; Черников, П.С. (Електротехніка і електромеханіка, 2017)
Целью работы является разработка метода расчета переходных режимов гребных электроэнергетических установок
в составе судовых пропульсивных комплексов. Методика. На маневрах продолжительности переходных режимов в
электроэнергетической установке соизмеримы с переходными режимами работы судна. Поэтому анализ маневренных режимов ее работы следует проводить в единстве со всеми составными частями судового пропульсивного комплекса. Результаты. Разработаны уточненная математическая модель и метод расчета переходных режимов всех
составных частей пропульсивного комплекса электрохода на маневрах. Найдены безразмерные параметры комплекса.
Они определяют основные показатели качества маневрирования. Адекватность модели и метода расчета подтверждены сравнением результатов математического моделирования с натурными экспериментами. Научная новизна.
Метод расчета позволяет рассчитывать динамические режимы работы всех составных частей комплекса. Появляется возможность проектирования гребных электроэнергетических установок по конечному результату – по показателям качества маневрирования судна. Практическое значение. Метод расчета позволяет проводить исследования
поведения пропульсивных комплексов на маневрах и отыскивать пути повышения маневренности электроходов. Метою роботи є розробка метода розрахунку перехідних режимів гребних електроенергетичних установок у складі
суднових пропульсивних комплексів. Методика. На маневрах тривалості перехідних режимів в електроенергетичній
установці сумірні з перехідними режимами роботи судна. Тому аналіз маневрених режимів її роботи слід проводити в
єдності з усіма складовими частинами суднового пропульсивного комплексу. Результати. Розроблені уточнена математична модель і метод розрахунку перехідних режимів всіх складових частин пропульсивного комплексу електрохода на маневрах. Знайдено безрозмірні параметри комплексу. Вони визначають основні показники якості маневрування.
Адекватність моделі і методу розрахунку підтверджено порівнянням результатів математичного моделювання з
натурними експериментами. Наукова новизна. Метод розрахунку дозволяє розраховувати динамічні режими роботи
всіх складових частин пропульсивного комплексу. З'являється можливість проектування гребних електроенергетичних установок по кінцевому результату – за показниками якості маневрування судна. Практичне значення. Метод
розрахунку дозволяє проводити всебічні дослідження пропульсивних комплексів на маневрах і знаходити можливості
підвищення маневреності електроходів. Б The purpose of the work is to develop the method for calculating
the transient modes of electric ships’ propelling electric plants
during maneuver. This will allow us to evaluate and improve the
maneuverability of vessels with electric motion. Methodology. The
solution to the problems is proposed to be carried out on the basis
of mathematical modeling of maneuvering modes. The duration of
transient modes in an electric power plant at electric ships’ maneuvers is commensurable with the transient operation modes of
the vessel itself. Therefore, the analysis of the electric power
plants’ maneuvering modes should be made in unity with all the
components of the ship’s propulsion complex. Results. A specified
mathematical model of transient regimes of electric ship’s propulsion complex, including thermal motors, synchronous generators,
electric power converters, propulsion motors, propellers, rudder,
ship’s hull is developed. The model is universal. It covers the vast
majority of modern and promising electric ships with a traditional
type of propulsors. It allows calculating the current values of the
basic mode indicators and assessing the quality indicators of
maneuvering. The model is made in relative units. Dimensionless
parameters of the complex are obtained. These parameters influence the main indicators of the quality of maneuvering. The adequacy of the suggested specified mathematical model and the
developed computation method based on it were confirmed. To do
this, the results of mathematical modeling for a real electric ship
were compared with the data obtained in the course of field experiments conducted by other researchers. Originality. The
mathematical description of a generator unit, as an integral part
of an indivisible ship’s propulsion complex, makes it possible to
calculate the dynamic operation modes of electric power sources
during electric vessels’ maneuvering. There is an opportunity to
design the electric ships’ propulsion power plant according to the
final result – according to the indicators characterizing the vessel
and its maneuvering properties. The use of a system of dimensionless units provides a generality to the results obtained. Electric ships with equal values of dimensionless parameters will have
correspondingly the same values (in relative units) of maneuvering quality indicators. Practical value. The developed mathematical model and the research method constructed on its basis allow
calculating the current values of the basic regime parameters of
all the components of the ship’s propulsion complex. A mathematical apparatus for estimating the main indicators of the quality
of electric ships’ maneuvering is proposed. There is an opportunity to improve the electric ships’ maneuvering characteristics by
optimizing the operation of propulsion motors.